Intelligence and Medial Temporal Lobe Function in Older Adults: A Functional MR Imaging–Based Investigation - Yousem, D.M.; Yassa, M.A.; Cristinzio, C.; Kusevic, I.; Mohamed, M.; Caffo, B.S.; Bassett, S.S. (American Journal of Neuroradiology, 2009)
BACKGROUND AND PURPOSE: The influence of general intelligence and formal education on functional MR imaging (fMRI) activation has not been thoroughly studied in older adults. Although these factors could be controlled for through study design, this approach makes sample selection more difficult and reduces power. This study was undertaken to examine our hypothesis that intelligence and education would impact medial temporal lobe (MTL) fMRI responses to an episodic memory task in healthy elderly subjects. MATERIALS AND METHODS: Thirty-six women and 38 men, 50–83 years of age (mean, 63.4 ± 7.9 years), completed an auditory paired-associates paradigm in a 1.5T magnet. The amplitude and volume of fMRI activation for both the right and left MTLs and MTL subregions were correlated with the intelligence quotients (IQs) and educational levels by using Pearson correlation coefficient tests and regression analyses. RESULTS: The participants' mean estimated full scale IQ and verbal IQ scores were 110.4 ± 7.6 (range, 92–123) and 108.9 ± 8.7 (range, 88–123), respectively. The years of education showed a mean of 16.1 ± 3.2 years (range, 8–25 years). The paradigm produced significant activation in the MTL and subregions. However, the volume and amplitude of activation were unrelated to either IQ or years of schooling in men and/or women. CONCLUSIONS: We found no evidence of an effect of IQ or education on either the volume or amplitude of fMRI activation, suggesting that these factors do not necessarily need to be incorporated into study design or considered when evaluating other group relationships with fMRI.